Crenshaw's Intersectionality of Racial and Gender Discrimination of Black Women in The Six Triple Eight (2024) - Welastiningsih Sihombing; Maya Sekartaji (PT. Alahyan Publisher Sukabumi, 2026)
The representation of marginalized groups, particularly women and Black communities, has long been a central concern in social and cultural studies. This study examines the intersectionality of racial and gender discrimination experienced by Black women as depicted in The Six Triple Eight (2024), directed by Tyler Perry. Using a qualitative descriptive method within an interpretative film analysis framework, the research investigates how intersecting identities, specifically race, gender, and class; are constructed and represented through the film’s narrative and character development. Drawing on Kimberlé Crenshaw’s theory of intersectionality, the analysis focuses on selected scenes, dialogues, and character interactions involving members of the 6888th Central Postal Directory Battalion, the only all-Black, all-female military unit deployed overseas during World War II. The findings reveal key themes, including layered racial and gender discrimination, the resilience of Black women in confronting oppressive systems, collective solidarity among unit members, and the historical invisibility of their contributions. Furthermore, the study demonstrates how the film contributes to broader discussions on intersectional identity and the representation of marginalized groups. Overall, the findings suggest that The Six Triple Eight not only brings attention to the historically overlooked role of Black women in military history but also functions as a cinematic medium for reclaiming and preserving historical memory.